2020
DOI: 10.1038/s41467-020-18857-z
|View full text |Cite
|
Sign up to set email alerts
|

The ALPK1/TIFA/NF-κB axis links a bacterial carcinogen to R-loop-induced replication stress

Abstract: Exposure of gastric epithelial cells to the bacterial carcinogen Helicobacter pylori causes DNA double strand breaks. Here, we show that H. pylori-induced DNA damage occurs co-transcriptionally in S-phase cells that activate NF-κB signaling upon innate immune recognition of the lipopolysaccharide biosynthetic intermediate β-ADP-heptose by the ALPK1/TIFA signaling pathway. DNA damage depends on the bi-functional RfaE enzyme and the Cag pathogenicity island of H. pylori, is accompanied by replication fork stalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 76 publications
2
65
0
1
Order By: Relevance
“…In particular, we found that the biosynthesis of ADP-heptose and the key gene hldE were significantly enriched in adenoma compared with control. ADP-heptose has been identified as a bacteria-linked carcinogen 36 and the key metabolic intermediate in the biosynthesis of LPS. It is a potent trigger for the activation of NF-κB signaling, which has been shown to promote tumorigenesis 37 and may be critical in perpetuating inflammation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found that the biosynthesis of ADP-heptose and the key gene hldE were significantly enriched in adenoma compared with control. ADP-heptose has been identified as a bacteria-linked carcinogen 36 and the key metabolic intermediate in the biosynthesis of LPS. It is a potent trigger for the activation of NF-κB signaling, which has been shown to promote tumorigenesis 37 and may be critical in perpetuating inflammation 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies focus on ways by which bacteria can contribute to colorectal cancer initiation and progression beyond the induction of mutations. Several non-intestinal organoid systems have been used to pinpoint bacterially driven activation of cancerassociated pathways, aberrant proliferation, and replication stress (Bauer et al, 2020;McCracken et al, 2014;Scanu et al, 2015). We anticipate that applying these methods to colorectal cancer organoids will reveal further causal relationships.…”
Section: Dna Damage Mutagenesis and Cancermentioning
confidence: 99%
“…The exact mechanism for the putative role of CagA in gastric carcinogenesis is still disputed [ 11 ], but it has been proposed that CagA produces an oncoprotein which could induce malignancy after being incorporated into a cell [ 12 ]. Alternatively, exposure of H. pylori carcinogen in vitro has been reported to induce DNA damage [ 13 ]. However, these two mechanisms presently lack support from convincing in vivo data.…”
Section: Gastric Cancermentioning
confidence: 99%